Manajemen Kerjasama Internasional dalam Kursus Bahasa Arab Intensif - Najmi, Nurun; Mufidah, Nuril (Pedagogi: Jurnal Ilmu Pendidikan, 2024)
Course institutions need good program management to be able to create Arabic language learning in accordance with the goals and objectives. Learning management itself has four functions: planning, organizing, implementing, and controlling. This research aims to describe the planning, organizing, mobilization and management control of the An-Najah Center Course Program in Medan, Indonesia. This research uses a qualitative descriptive research method. Data collection techniques include observation of Arabic language program activities, interviews with course founders and teachers, and documentation. The data collected was analyzed using descriptive data in three main steps, namely data reduction, data exposure, and conclusion drawing. The research results show that planning starts with analyzing needs, classifying student competencies, formulating learning objectives, designing the curriculum and syllabus, and determining teaching materials.